The developing teaching practice model as an effort to improve the quality of mechanical engineering vocational school teachers - Theodorus Wiyanto; Muchlas Samani; Sugiyono Sugiyono (Jurnal Pendidikan Vokasi, 2017)
This research aims to develop teaching practice program model for mechanical engineering education teacher trainees of State University of Surabaya. This research applied research and development (R & D) design by Borg & Gall in ten steps which are classified into two stages: research and data collection and product development. The research and data collection were conducted by applying qualitative approach through observation, interview, documentation on seven State "˜LPTK', education office, teacher profession association, teaching practice student, teaching practice supervising lecturer, headmaster, and teacher tutor. The data analysis in this stage was conducted based on the technique developed by Miles and Huberman. Data validity was tested with data triangulation using double sources as comparison. The product development stage included model pre-design making, introductory test, model revision, model test, model revision, field test, and final model revision. First stage model test was conducted in mechanical engineering department with three vocational schools. The second stage model test was conducted in mechanical engineering department with six vocational schools. The last  is dissemination stage in the form of spreading the model yielded from the product development to professionals, authorities, and policy makers. The result at this research is a teaching practice model called "KPrIP2" which consists of four main product components. "K" means partnership between Mechanical Engineering Department of State University of Surabaya and the education office of province/ regency/city in continuous planning, action, and evaluation. "Pr" means pre-teaching practice in which the students do introductory activities in vocational schools to observe and coordinate with the school's department to determine who will be the teacher tutor and what material/subject to be used in the teaching practice II. "I" means that all pre-teaching practice activities, starting from classroom peer-teaching, laboratory peer-teaching, microteaching, and real teaching in vocational school, are conducted individually and independently. "P2" means that teaching service activities must be supervised by competent/professional advisors, i.e. who have the same pedagogical and major background with the students who do the teaching practice and play role as the supervising lecturer of teaching practice I which is continued to be the advisor in teaching practice II. Teaching practice model "KPrIP2" is claimed to be effective to reach the teaching practice objectives but inefficient in budgeting.